Growth inhibition of Pseudomonas aeruginosa using products of some probiotic microorganisms and secondary metabolites of Commiphora myrrha extracts estimated by GC-MS technique - Teeba Hashim Mohammad; Zina Hashem Shehab; Arwa A. Tawfiq (مجلة بغداد للعلوم)
The search for new antibacterial agents is necessary due to the limited availability of effective treatments to treat bacterial infections. The current study aimed to study the utilization of the products of some probiotic microorganisms, such as Lactobacillus acidophilus and Saccharomyces boulardii, are cultured on solid and liquid media, as well as examining the biological activity of the secondary metabolites of the aqueous, alcoholic, and vinegar extracts of the Commiphora myrrha (Myrrh) plant, and honey on the growth of five clinical isolates of Pseudomonas aeruginosa isolated from wounds using the diffusion method with tablets. Some chemical tests were conducted to identify the effective compounds of the extracts using qualitative analysis of the chemical compounds in the plant. In addition to the high antioxidant effect, which was recorded at about 64.84, the results of the Gas Chromatography-Mass Spectrometry (GC-MS) is an analysis to identify different substances into compounds in aqueous extract and ethanolic. The results of aqueous, alcoholic, vinegar and honey extracts of C. myrrha showed that all studied extracts have the ability to inhibit P. aeruginosa, but to different extents. The aqueous extract gave better results than the alcoholic extracts, and vinegar. As for honey, it did not have a synergistic inhibitory effect when mixed with the myrrh plant extract.  As for L. acidophilus had an inhibitory effect on growth in solid agar for all tested isolates, while the use of bacterial free- cell supernatant did not show any inhibitory activity against bacteria